2012
DOI: 10.5897/ajpp12.366
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antitumour action of Ganoderma lucidum extract in hepatocarcinoma mice

Abstract: The present study shows the protective effects of the Ganoderma lucidum aqueous crude extract (GLE) against mice liver cancer. The mice were randomized into four groups, namely, controls and tumor bearers that were G. lucidum extract-treated or untreated. Tumor bearers were inoculated intraperitoneally (ip) with 108 Yoshida AH-130 ascites hepatoma cells, whereas the controls received saline alone. The treatment began 1 day after tumor cell inoculation, and continued for 14 days. Administration of G. lucidum ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Different administration protocols of GLP can lead to up to 60 % inhibition of S180 xenografts in mice without obvious adverse effect on body weight [39, 53]. In Yoshida AH-130 ascites hepatoma cells implemented mice, administration of an aqueous extract of G. lucidum reduces the tumor weight in a dose dependent manner compared to the control group, with inhibition rates of 25% and 47% at 200 and 400 mg/kg, respectively [67]. GLP significantly suppresses tumor growth in hepatoma-bearing mice associated with an increase of the ratio of regulatory T cell (Treg) and effector T cell (Teff).…”
Section: Anticancer Effects Of Glpmentioning
confidence: 99%
See 1 more Smart Citation
“…Different administration protocols of GLP can lead to up to 60 % inhibition of S180 xenografts in mice without obvious adverse effect on body weight [39, 53]. In Yoshida AH-130 ascites hepatoma cells implemented mice, administration of an aqueous extract of G. lucidum reduces the tumor weight in a dose dependent manner compared to the control group, with inhibition rates of 25% and 47% at 200 and 400 mg/kg, respectively [67]. GLP significantly suppresses tumor growth in hepatoma-bearing mice associated with an increase of the ratio of regulatory T cell (Treg) and effector T cell (Teff).…”
Section: Anticancer Effects Of Glpmentioning
confidence: 99%
“…Many studies have demonstrated that GLP has the ability to inhibit angiogenesis. It has been shown that GLP suppresses VEGF overexpression and tumor angiogenesis in metastatic mouse melanoma B16F10 cells in vitro and Yoshida AH-130 ascites hepatoma xenografts in vivo [34, 67]. GLP peptide markedly reduces the microvessel formation as detected by chorioallantoic membrane assay [76].…”
Section: Anticancer Effects Of Glpmentioning
confidence: 99%
“…Nevertheless, many bioactive compounds in G. lucidum exhibit antioxidant, antitumor, and anti-inflammatory properties [32][33][34][35][36][37]. Such benefits have been investigated in multiple studies on their effect against prostate cancer, ovarian cancer, hepatocellular carcinoma, the induction of apoptosis in colon cancer, and the inhibition of angiogenesis [38][39][40][41][42][43]. Different immunomodulatory activities have been reported [44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%